2005
DOI: 10.1128/jcm.43.1.140-143.2005
|View full text |Cite
|
Sign up to set email alerts
|

Synergy Tests by E Test and Checkerboard Methods of Antimicrobial Combinations against Brucella melitensis

Abstract: Two different synergy testing methods, the checkerboard and the E test methods, were used to compare the in vitro efficacies of various antimicrobial combinations against 16 Brucella melitensis strains isolated from blood cultures. The rate of agreement of the E test and checkerboard methods was found to be 55%. The most concordant results were found for the streptomycin-doxycycline combination in 12 (75%) tests, in which four strains showed synergistic activity by E test and antagonistic activity by the check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
299
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(307 citation statements)
references
References 3 publications
3
299
3
2
Order By: Relevance
“…On the contrary, the agreement of time-kill assay with the other 3 methods was low. In general, the agreements obtained in the literature are diverse (Bonapace et al, 2000;Cantón et al, 2005;Lewis et al, 2002;Martin, 2010;Orhan et al, 2005;White et al, 1996). However, a variety of investigators found disagreement between checkerboard and time-kill results (Cappelletty and Rybak, 1996;Chang et al, 2007;Visalli et al, 1988;White et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, the agreement of time-kill assay with the other 3 methods was low. In general, the agreements obtained in the literature are diverse (Bonapace et al, 2000;Cantón et al, 2005;Lewis et al, 2002;Martin, 2010;Orhan et al, 2005;White et al, 1996). However, a variety of investigators found disagreement between checkerboard and time-kill results (Cappelletty and Rybak, 1996;Chang et al, 2007;Visalli et al, 1988;White et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Combinations of the concentrations below each MIC level that caused complete inhibition of microbial growth of L. monocytogenes were evaluated across serial dilutions of enterocin A and thyme EOs by checkerboard technique using a sterile 96-well microplates and BHI broth (Orhan et al 2005;NCCLS 2003). All aliquots were prepared using the same solvents (acetonitrile + BHI) as in the MIC assay and blank solutions containing the solvent at concentrations equivalent to those in the test solutions were also prepared.…”
Section: Determination Of Synergy Between Enterocin a And Thyme Eosmentioning
confidence: 99%
“…Fractional inhibitory concentration index (ƩFIC) for rapamycin and metformin combinations was determined as a measurement of drug interaction between the two compounds. The combination is considered synergistic when the ΣFIC is ≤ 0.5, non-synergistic when the ΣFIC is ≥ 0.5 and ≤ 4, and antagonistic when ΣFIC is ≥ 4 [28,29]. Rapamycin and metformin ΣFIC was 0.84 ± 0.09, suggesting non-synergistic interaction between the two compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Mode of drug interaction in combinations of biguanides and antifungals were determined by assessing the fractional inhibitory concentration index (ΣFIC) through the checkerboard method [28]. Following inoculation, checkerboard plates were incubated at 35°C and read at 560/590nm fluorescence after 18 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation